Pengaruh Purnajual dan Kualitas Pelayanan terhadap Loyalitas Konsumen Indihome Pt. Telkom Indonesia Medan (Studi pada Masyarakat Kota Medan) - Fathurahman Noeryakin; Faisal Eriza (Regress: Journal of Economics & Management, 2022)
This article aims to analyze that after sales have an effect on consumer loyalty Indihome in the city of Medan. Second, to analyze the effect of service quality on consumer loyalty Indihome in the city of Medan. Third, to analyze the effect of after-sales and service quality on the loyalty of Indihome consumers to the people in the city of Medan. This study used 96 respondents as a sample, using purposive sampling. The analytical method used is quantitative analysis which includes multiple linear regression analysis, T-test, F-test, and coefficient of determination test. The test was carried out using SPSS 25. The results of data analysis showed that there was a positive and significant service effect between after-sales and quality. The results of this study indicate that if there is a change in the independent variables after sales and service quality, there will also be changes in consumer loyalty. This is indicated by the results of the Adjusted R Square analysis of 0.615, which means that after-sales and service quality have an influence on consumer loyalty as much as 61.5%, while the remaining 38.5% is influenced by other variables not examined in this study.